The evolution of the liver transplant candidate - Hann, Angus; Neuberger, James (Frontiers in Transplantation, 2023)
The first successful human liver transplant (LT) was done over 60 years ago; since the early pioneering days, this procedure has become a routine treatment with excellent outcomes for the great majority of recipients. Over the last six decades, indications have evolved. Use of LT for hepatic malignancy is becoming less common as factors that define a successful outcome are being increasingly defined, and alternative therapeutic options become available. Both Hepatitis B and C virus associated liver disease are becoming less common indications as medical treatments become more effective in preventing end-stage disease. Currently, the most common indications are alcohol-related liver disease and metabolic associated liver disease. The developing (and controversial) indications include acute on chronic liver failure, alcoholic hepatitis and some rarer malignancies such as non-resectable colorectal cancer liver metastases, neuroendocrine tumours and cholangiocarcinoma. Candidates are becoming older and with greater comorbidities, A relative shortage of donor organs remains the greatest cause for reducing access to LT; therefore, various countries have developed transparent approaches to allocation of this life saving and life enhancing resource. Reliance on prognostic models has gone some way to improve transparency and increase equity of access but these approaches have their limitations.